Chromosomal Translocations and Genome Rearrangements in Cancer - Rowley, Janet D.; Rowley, Janet D.; Le Beau, Michelle M.; Le Beau, Michelle M.; Rabbitts, Terence H.; Rabbitts, Terence H. (Springer International Publishing : Imprint: Springer, 2015)
This volume collates world experts’ insights into the molecular biology of cancer chromosomes, their abnormalities and the subsequent cellular consequences. Exploring themes involving oncogenes, such as by chromosomal translocations, other genome rearrangements and somatic mutations, this book is a review of the field of cancer genetics that presages a new era, as whole genome sequencing becomes more accessible. The work begins with a look at historical themes, such as the analysis of metaphase chromosomes using microscopy and staining techniques, advances in which provided our first broad glimpse into the genetic anatomy of a malignant cell. Readers will learn about the application of DNA molecular cloning techniques in the 1980s, that led to the identification of the genes involved in the Philadelphia and Burkitt's lymphoma chromosomal translocations, solidifying the role of oncogenes and tumour suppressor genes in cancer aetiology via chromosomal alterations, and which launched a field in cancer genetics. Subsequent chapters bring the reader up to date by reviewing recent developments in the field, with dedicated sections on leukaemia/lymphoma, sarcomas and epithelial tumours. Contributions feature numerous colour tables and illustrations and this volume will provide a basis for understanding cancer chromosomes for many years to come.